2023
DOI: 10.1039/d2na00544a
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic and morphological characterization of heteropolymer human ferritin cores

Abstract: The physical properties of in vitro iron-reconstituted and genetically engineered human heteropolymer ferritins were investigated. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), electron energy-loss spectroscopy (EELS), and 57Fe Mӧssbauer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In an earlier study 27 , we showed that L-rich ferritins exhibit spherical and large iron cores with an average diameter of ~ 5.9 nm, whereas H-rich ferritins present elongated, dumbbell, and crescent-shaped cores with an average core diameter of ~ 3.7 nm, suggesting a significant correlation between protein shell composition, iron core shape, and likely biological function [1][2][3][4][5]59 . Such structural differences may offer unique characteristics to isoferritins and contribute to the functional diversity of ferritins in terms of iron accessibility to cells and protection against oxidative stress.…”
Section: Data Availabilitymentioning
confidence: 83%
See 2 more Smart Citations
“…In an earlier study 27 , we showed that L-rich ferritins exhibit spherical and large iron cores with an average diameter of ~ 5.9 nm, whereas H-rich ferritins present elongated, dumbbell, and crescent-shaped cores with an average core diameter of ~ 3.7 nm, suggesting a significant correlation between protein shell composition, iron core shape, and likely biological function [1][2][3][4][5]59 . Such structural differences may offer unique characteristics to isoferritins and contribute to the functional diversity of ferritins in terms of iron accessibility to cells and protection against oxidative stress.…”
Section: Data Availabilitymentioning
confidence: 83%
“…They may also affect and influence the interactions of ferritins with other protein partners and have important implications on many physiological processes including intracellular signaling and the pathogenesis of diseases. For instance, we have found that the smaller and elongated iron core diameter in H-rich ferritins exhibit a higher degree of crystallinity compared with L-rich cores which appear more diffuse and amorphous 27 . The less crystalline and low mineral order of L-rich ferritins iron cores is suggested to facilitate rapid iron turnover in support of the physiological role of these types of protein as a general iron source 47 .…”
Section: Data Availabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Magnetite particles smaller than 8 nm are not considered useful for magnetic hyperthermia (Fantechi et al, 2015). Because the size of the ferritin iron core is less than 5 nm in diameter (Longo et al, 2022), and because ferric hydroxide nanomaterial in native ferritin has ~8‐fold lower magnetic susceptibility compared to magnetite (Zborowski et al, 1996), the heating rate for ferritin is too low to be measurable and thus could not explain the observed significant drop in stability.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, ferritin is a heteropolymer consisting of a heavy chain subunit (H) and a light chain subunit (L), with the H/L ratio varying depending on the tissue. , The H chain possesses a ferroxidase center in its four-helix bundle, while the L chain lacks this center but contains a nucleation site located on its inner surface. A significant correlation exists between protein shell composition, iron core shape, and biological function. Previous studies have confirmed that Fe–O NPs formed by human and horse L-ferritins (HuLF and HoLF) have crystallinity and magnetic order. , Time-lapse anomalous X-ray diffraction has been confirmed to be very effective in the study of iron translocation in ferritin . Recently, Turano et al observed some status of Fe–O NCs in natural HuLf and HoLF using this method.…”
Section: Introductionmentioning
confidence: 95%